Current detection rates and time-to-detection of all identifiable BRCA carriers in the Greater London population. Issue 8 (5th April 2018) - Manchanda, Ranjit; Blyuss, Oleg; Gaba, Faiza; Gordeev, Vladimir Sergeevich; Jacobs, Chris; Burnell, Matthew; Gan, Carmen; Taylor, Rohan; Turnbull, Clare; Legood, Rosa; Zaikin, Alexey; Antoniou, Antonis C; et al.
Abstract : Background: BRCA carrier identification offers opportunities for early diagnoses, targeted treatment and cancer prevention. We evaluate BRCA- carrier detection rates in general and Ashkenazi Jewish (AJ) populations across Greater London and estimate time-to-detection of all identifiable BRCA carriers. Methods: BRCA carrier data from 1993 to 2014 were obtained from National Health Service genetic laboratories and compared with modelled predictions of BRCA prevalence from published literature and geographical data from UK Office for National Statistics. Proportion of BRCA carriers identified was estimated. Prediction models were developed to fit BRCA detection rate data. BRCA carrier identification rates were evaluated for an 'Angelina Jolie effect'. Maps for four Greater London regions were constructed, and their relative BRCA detection rates were compared. Models developed were used to predict future time-to-identify all detectable BRCA carriers in AJ and general populations. Results: Until 2014, only 2.6% (3072/111 742 estimated) general population and 10.9% (548/4985 estimated) AJ population BRCA carriers have been identified in 16 696 608 (AJ=190 997) Greater London population. 57% general population and 54% AJ mutations were identified through cascade testing. Current detection rates mirror linear fit rather than parabolic model and will not identify all BRCA carriers. Addition of unselected ovarian/triple-negative breast cancer testing would take >250 years to identify all BRCA carriers. Doubling current detection rates can identify all 'detectable' BRCA carriers in the general population by year 2181, while parabolic and triple linear rates can identify 'detectable' BRCA carriers by 2084 and 2093, respectively. The linear fit model can identify 'detectable' AJ carriers by 2044. We did not find an Angelina Jolie effect on BRCA carrier detection rates. There was a significant difference in BRCA detection rates between geographical regions over time (P<0.001). Conclusions: The majority of BRCA carriers have not been identified, missing key opportunities for prevention/earlier diagnosis. Enhanced and new strategies/approaches are needed.